Potensi Limbah Daun Asam Jawa (Tamarandus Indica L.) Sebagai Teh Antidiare: Potential Waste of Tamarind Leaves (Tamarandus Indica L.) As Antidiarrheal Tea - Dwi Kartika Risfianty; Irna Il Sanuriza (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2022)
Diarrhea is an increased frequency and decreased consistency of stool when compared to normal individuals. Giving chemical medicine which  consumed continuously, can cause negative side effects for the body. So it takes an effort to find sources of anti-diarrheal medicine that minimize side effects to the body. One source of medicine that can reduce side effects on the body is traditional medicine from local plants. One of the efforts to find a new source of anti-diarrheal medicine is to use tamarind leaves (Tamarindus indica L.) which will be developed into an anti-diarrheal bioagent. This study aims to determine the effectiveness of giving water extract of tamarind leaves (Tamarindus indica L.) fresh old leaves and young leaves to the experimental male Mus musculuus diarrhea positive. This research used three stages of research, namely the preparation of fresh old leaves and young leaves tamarind (Tamarindicus indica L.) leaf water extract, extract testing using 1% FeCl3 and UV-VIS spectrophotometer and testing using male Mus muscullus experimental animals. The results of this study indicate that the tannin content contained in the water extract of tamarind leaves (Tamarindus indica L.) is higher based on testing using 1% FeCl3 and UV-VIS septrophotometer and is more effective in overcoming diarrhea in experimental animals Mus muscullus based on changes in fecal consistency animal try to the Mus muscullus.  Key words: diarrhea; tannins; tamarind; water extract